Differential Utilization Patterns of Total Ankle Arthroplasty vs Arthrodesis: A United States National Ambulatory Database Analysis - Michael R. Mercier MD, MHS; Philip P. Ratnasamy BS; Nicholas S. Yee MD; Brandon Hall MDCM; Christopher Del Baso MBBS, MSci; Mohammed Athar MD; Timothy R. Daniels MD; Mansur M. Halai MBChB (Foot & Ankle Orthopaedics, 2023)
Background: End-stage ankle osteoarthritis is a condition that can be treated with ankle arthrodesis (AA) or total ankle arthroplasty (TAA). The goal of this study is to estimate the 2016-2017 United States’ utilization of TAA and AA in specific ambulatory settings and delineate patient and hospital factors associated with the selection of TAA vs AA for treatment of ankle osteoarthritis. Methods: TAA and AA procedures performed for ankle osteoarthritis were identified in the 2016-2017 Nationwide Ambulatory Surgery Sample (NASS) Database. Notably, the NASS database only examines instances of ambulatory surgery encounters at hospital-owned facilities. As such, instances of TAA and AA performed at privately owned or freestanding ambulatory surgical centers or those performed inpatient are excluded from this analysis. Cases were weighted using nationally representative discharge weights. Univariate analyses and a combined multiple logistic regression model were used to compare demographic, hospital-related, and socioeconomic factors associated with TAA vs AA. Results: In total, 6577 cases were identified, which represents 9072 cases after weighting. Of these, TAA was performed for 2233 (24.6%). Based on the logistic regression model, several factors were associated with increased utilization of TAA vs AA. With regard to patient factors, older patients were more likely to undergo TAA, as well as females. Conversely, patients with a higher comorbidity burden were less likely to receive TAA over AA. With regard to socioeconomic factors, urban teaching and urban nonteaching hospitals were significantly more likely to use TAA compared to rural hospitals. Similarly, privately insured patients and those with a median household income of $71 000 or more were also more likely to receive TAA over AA. Private hospitals (“not-for-profit” and “investor-owned”) were significantly more likely to offer TAA over AA. Conclusion: Using a large nationally representative cohort, the current data revealed that during 2016-2017, 24.6% of operatively treated cases of end-stage ankle osteoarthritis in the ambulatory setting are treated with TAA. Associations between socioeconomic and hospital-level factors with TAA utilization suggest that nonclinical factors may influence surgical treatment choice for ankle osteoarthritis. Level of Evidence: Level III, retrospective cohort study.